2021
DOI: 10.1007/s12178-021-09701-y
|View full text |Cite|
|
Sign up to set email alerts
|

Interval Return to Play Programs for the Tennis Athlete

Abstract: Purpose of Review General guidelines exist for return to sport after injury. The goal of these guidelines is to outline phases of recovery that will minimize the risk of reinjury and promote an optimal return to function for the athlete. This paper analyzes the current research pertaining to interval return to play programs with a special focus on the tennis athlete. The authors examine the different components of an interval tennis program and work to develop what they feel are the necessary ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Therefore, conservative methods, such as rehabilitation are commonly employed for tennis athletes hoping to return to sport after a shoulder injury. An interval return program is one of many rehabilitation techniques designed to return an athlete back to their level of play 11 . However, to date, there is a paucity of research on conservative RIA rehabilitation for elitelevel tennis athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, conservative methods, such as rehabilitation are commonly employed for tennis athletes hoping to return to sport after a shoulder injury. An interval return program is one of many rehabilitation techniques designed to return an athlete back to their level of play 11 . However, to date, there is a paucity of research on conservative RIA rehabilitation for elitelevel tennis athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The International Tennis Association Tennis Rating Exam measures a player's strength. 4 The depth and accuracy of the baseline shot are the essential criteria for measuring the quality of a tennis player's shot. The above two indicators can well reflect the quality of a player's batting.…”
Section: Itn Testmentioning
confidence: 99%
“…Recent studies using isokinetic testing devices and hand-held dynamometry tests have suggested normative values for comparisons between various muscle groups and side-to-side differences. At isokinetic velocity of 60°•s −1 and 240°•s −1 peak torque ratios of 63% to 72% for shoulder ER/IR and an isometric ER/IR ratio of 75% to 100% (depending on the testing position) are recommended (24)(25)(26)(27). In terms of side-to-side differences, a 10% higher strength of the external rotators and internal rotators is expected for the throwing shoulder when compared with the nondominant side in uninjured athletes (3).…”
Section: Strength Testingmentioning
confidence: 99%
“…Supervised sports activity progression has been used to make the final decision to RTS in baseball and tennis (24,25,36). Progressive throwing and serving programs which monitor symptoms and increase volume and intensity of activity over several weeks should be included in the decision-making process.…”
Section: Supervised Sports Activity Progressionmentioning
confidence: 99%